2D Nanomaterials: Hybrids of Fullerenes and 2D Nanomaterials (Adv. Sci. 1/2019). Issue 1 (9th January 2019) - Chen, Muqing; Guan, Runnan; Yang, Shangfeng
Abstract : By hybridizing covalently or noncovalently fullerenes with 2D nanomaterials such as graphene, molybdenum disulfide (MoS2 ) and black phosphorus (BP), the unique properties of 2D nanomaterials can be tailored and improved, significantly extending their functionalities and applications. In article number1800941, Shangfeng Yang and co‐workers exhaustively review all types of hybrids of fullerenes and 2D nanomaterials, emphasizing their versatile hybridization strategies and applications.